The transformation of political elites in the European Union after 2008. What is next after the constraining dissensus?. Issue 4 (19th May 2021) - Sus, Monika; Hadeed, Marcel
ABSTRACT: The European Union has witnessed a transformation of national political elites in the last decade. In addition to local factors, this is caused by a range of broader societal and political discontinuities. By applying Higley's model of political elite transformation to the Eurozone- and migration crises, we reveal the nature of this transformation: political elites today are more differentiated and less united than a decade ago. The analysis shows that the discontinuities brought forth newly founded political parties and strengthened those with previously little voice in decision-making. These new elites reflect the Euroscepticism of an increasing proportion of their constituency. Thus, we argue that the European political landscape has moved beyond the constraining dissensus to a post-constraining dissensus, where national elites themselves challenge European integration. As elite transformation continues, the process of European integration will have to grapple with the realities of increased elite diversity for the foreseeable future.